A Igreja Católica e a transformação do espaço e do viver urbano de Pouso Alegre-MG (1936-45) - Sampaio, Carlos Leonardo Teixeira (2009)
This dissertation entitled: "The Catholic Church and the transformation of urban space and living in Pouso Alegre- MG (1936 - 45)" seeks to discuss the position and articulation adopted by the Diocese of Pouso Alegre, on the change in area of the city, which was effective interventions for urban. Also reflect the position held by the Church for the arrival of new costumes influenced mainly by the arrival of cinema sound and a greater presence in the region of other religions. In this perspective, analyze the church's emphasis on control and educational intervention on female youth and children, serving as an instrument of defense of their institution. The local press, but also books of memories of the city are the main sources used in the discussion of the topic. The work is divided into three parts: the first, discuss the Catholic Church before the changes of the spaces of the city, the second part, discusses the issue of Catholic moral and female youth, given the transformations in urban life and ultimately, the church and infant universe in its educational and discussion on the social problem of children in Pouso Alegre